2009
DOI: 10.1007/s00330-009-1311-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous treatment of intrabdominal abscess: urokinase versus saline serum in 100 cases using two surgical scoring systems in a randomized trial

Abstract: The purpose of this study was to assess whether regular instillation of urokinase during abscess drainage leads to an improved outcome compared to saline irrigation alone. One hundred patients referred for image-guided abdominal abscess drainage were randomized between thrice daily urokinase instillation or saline irrigation alone. At the end of the study, patient medical records were reviewed to determine drainage, study group, Altona (PIA II) and Mannheim (MPI) scoring, duration of drainage, procedure-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
14
0
9
Order By: Relevance
“…Furthermore, S. aureus bacteria in the caseous pus were not completely killed after incubation in AA for 10 min. Thus, the experimental results of the present study suggested that AA can only perform limited osmosis and bactericidal effect in the caseous pus (17).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Furthermore, S. aureus bacteria in the caseous pus were not completely killed after incubation in AA for 10 min. Thus, the experimental results of the present study suggested that AA can only perform limited osmosis and bactericidal effect in the caseous pus (17).…”
Section: Discussionmentioning
confidence: 47%
“…However, it is difficult to aspirate or drain pus, and to select the appropriate antibiotic treatment when the abscess has thick pus and polymicrobial co-infection, or its pathogenic bacteria are multidrug resistant and cryptogenic in origin (8,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…O ile początkowo w ropniu mogą dominować bakterie tlenowe, o tyle w późniejszym okresie dochodzi zwykle do rozwoju bakterii beztlenowych [16,17]. Gruba torebka ropnia oraz postępująca redukcja jej ukrwienia doprowadza do ograniczenia możliwości przenikania antybiotyków do wnętrza zmiany [3,[16][17][18]. Dodatkowo bakterie wykształcają swoistą obronę przeciwko mechanizmom odpornościowym, co przy znacznym obniżeniu pH jest podstawową przyczyną braku skuteczności leczenia antybiotykami w przypadku ropni.…”
unclassified
“…Pod względem mikrobiologicznym rodzaj stwierdzanego patogenu zależy przede wszystkim od przyczyny ogniska ropnego, odpowiedzi organizmu i czasu infekcji [1,3,5,11,12,[15][16][17][18] oraz od miejsca usytuowania ropnia i możliwości nadkażenia, głównie za sprawą wtór-nych infekcji oraz zabiegowych procedur leczniczych [10,[17][18][19]. Z jamy ropnia hodowane są zwykle liczne patogeny.…”
unclassified
See 1 more Smart Citation